Core outcome sets for prevention and treatment of postpartum haemorrhage: an international Delphi consensus study. (29th July 2018) - Meher, S; Cuthbert, A; Kirkham, JJ; Williamson, P; Abalos, E; Aflaifel, N; Bhutta, ZA; Bishop, A; Blum, J; Collins, P; Devane, D; Ducloy‐Bouthors, A‐S; et al.
Abstract : Objective: To develop core outcome sets (COS) for studies evaluating interventions for (1) prevention and (2) treatment of postpartum haemorrhage (PPH), and recommendations on how to report the COS. Design: A two‐round Delphi survey and face‐to‐face meeting. Population: Healthcare professionals and women's representatives. Methods: Outcomes were identified from systematic reviews of PPH studies and stakeholder consultation. Participants scored each outcome in the Delphi on a Likert scale between 1 (not important) and 9 (critically important). Results were discussed at the face‐to‐face meeting to agree the final COS. Consensus at the meeting was defined as ≥ 70% of participants scoring the outcome as critically important (7–9). Lectures, discussion and voting were used to agree how to report COS outcomes. Main outcome measures: Outcomes from systematic reviews and consultations. Results: Both Delphi rounds were completed by 152/205 (74%) participants for prevention and 143/197 (73%) for treatment. For prevention of PPH, nine core outcomes were selected: blood loss, shock, maternal death, use of additional uterotonics, blood transfusion, transfer for higher level of care, women's sense of wellbeing, acceptability and satisfaction with the intervention, breastfeeding, and adverse effects. For treatment of PPH, 12 core outcomes were selected: blood loss, shock, coagulopathy, hysterectomy, organ dysfunction, maternal death, blood transfusion, use of additional haemostatic intervention, transfer for higher level of care, women's sense of wellbeing, acceptability and satisfaction with the intervention, breastfeeding, and adverse effects. Recommendations were developed on how to report these outcomes where possible. Conclusions: These COS will help standardise outcome reporting in PPH trials. Tweetable abstract: Core outcome sets for PPH: nine core outcomes for PPH prevention and 12 core outcomes for PPH treatment. Tweetable abstract: Core outcome sets for PPH: nine core outcomes for PPH prevention and 12 core outcomes for PPH treatment.